Influence of Nonmagnetic Dilution on the Magnetic Properties of La1−xDyxMn1−yZnyO3 Perovskites at High Temperature. Issue 15 (23rd December 2021) - López-Toro, José Fernando; Lezama, Luis; Salazar, Daniel; Mendoza, Aminta
Abstract : Herein, the influence of Zn nonmagnetic doping on magnetic properties above the Curie temperature of La1− x Dy x Mn1− y Zn y O3 diluted samples is studied. The Zn doping effect on the structure and distortions of MnO6 octahedra are observed, suggesting a relaxation effect of the tilting on the stress introduced by Zn doping. Magnetization versus temperature shows a transition from paramagnetic (PM) to ferromagnetic (FM) phase in the temperature range from 130 to 190 K. In the PM regime, FM spin clusters are observed by dc susceptibility and electron PM resonance (EPR). The effective moment of the clusters is obtained from the high‐temperature dc susceptibility. The effective exchange constants, J, are estimated using an open‐source program for the high‐temperature expansion (HTE) for inverse susceptibility χ − 1 of the spin Heisenberg model. Abstract : Doping of Dy 3+ ions on the short‐range magnetism of La1− x Dy x Mn y Zn1− y O3 manganites exhibits two competitive effects: Mn−O−Mn network distortion (Curie temperature decreases) and introduction of a random magnetic potential on Mn sublattice (Curie temperature increases). The predominance of one effect over the other is given by the lightly Zn‐doped Mn−O−Mn network.